Strong interfacial interaction significantly improving hydrogen evolution reaction performances of MoS2/Ti4O7 composite catalysts. (20th March 2020) - Zhao, Jianghong; Li, Wei; Wu, Shiping; Xu, Feifei; Du, Jiafeng; Li, Jiefeng; Li, Kaixi; Ren, Jun; Zhao, Yongxiang
Abstract: A catalytic non-carbon composite composed of molybdenum disulfide (MoS2 ) and conducting Magnéli phase Ti4 O7 is firstly synthesized by a facile hydrothermal method. The MoS2 /Ti4 O7 composite catalyst shows significantly improved hydrogen evolution reaction (HER) activity in 0.5 M H2 SO4 especially at high overpotentials mainly due to the fast electron transfer ability caused by the newly formed interfacial S–O–Ti bonds and the enhanced electrochemical surface area. Tafel slope of the optimized MoS2 /Ti4 O7 catalyst is as low as 48 mV · dec −1 . It also presents an impressive stability with smaller activity degradation (5 mV potential shift at 10 mA cm −2 ) after 1000 cycles of cyclic voltammetry (CV) scanning. This is the first exploration on HER performances of MoS2 and conductive metal oxide composite electrocatalysts, shedding light on the research of non-noble metal (sulphide)-metal oxide interface in energy catalysis significantly crucial for the development of cost-effective and stable HER electrocatalysts and even other electrocatalytic materials. Graphical abstract: Image 1